Integration of Visual Arts Methods in Education: Reducing Stress, Enhancing Introspection, and Emotional Well-being - Maja Žmukić; Martina Kosec; Jasna Bajraktarević; Viktor Gurović (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji, 2025)
Contemporary global trends, marked by increasing levels of stress and anxiety, underscore the need for innovative approaches in education, visual arts and therapy. The therapeutic potential of artistic activities within educational settings highlighting their contribution to stress reduction, enhancement of emotional and cognitive abilities. This study analyzes the impact of artistic activity on the emotional and cognitive state of students, with a focus on the therapeutic application of drawing as a method for reducing stress assessing their emotional states before and after participation in the exercises. The aim was to examine how artistic expression can affect emotional stability and to explore the potential of this method in the educational process. The workshop integrated artistic, pedagogical and therapeutic approaches, positioning drawing as a powerful tool for enhancing emotional well-being and cognitive abilities. The research included 21 participants, fourth year students, who took part in the art activity. Quantitative analysis showed that emotions related to happiness, such as “joyful,” increased by 52.89%, calmness by 47.93%, while negative emotions such as “nervous” decreased by 48.19%. A questionnaire revealed that 85.71% of participants felt relaxed after the workshop, while 100% reported a reduction in stress.